Admission albumin-globulin ratio associated with delayed cerebral ischemia following aneurysmal subarachnoid hemorrhage - Guo, Xiumei; Xiong, Yu; Gao, Wen; Huang, Xinyue; Zheng, Hanlin; Wu, Huiqiang; Jiang, Xutang; Lin, Qingxin; Xiao, Yinfeng; Liu, Qiaoling; Pan, Zhigang; Chen, Chunhui; et al. (Frontiers in Neurology, 2024)
Despite the widespread use in ischemic stroke, cancer, and malnutrition, the predictive ability of serum albumin to globulin ratio (A/G) among patients suffering from aneurysmal subarachnoid hemorrhage (aSAH) remains unknown. This study aimed to determine if serum A/G ratio is associated with the occurrence of delayed cerebral ischemia (DCI) after aSAH. Medical records of 363 patients with aSAH from August 2017 to August 2022 were reviewed, with DCI observed in 87 (23.97%) cases. Laboratory data for albumin and globulin levels were obtained within 24 h after admission. The serum A/G ratio was classified depending on the presence of DCI. The predictors of DCI were determined using logistic regression. Furthermore, receiver operating characteristic (ROC) curves were used to calculate the association between serum A/G levels and the incidence of DCI. Serum A/G, non-surgical treatment, lactate dehydrogenase (LDH), phosphorous, and plasma fibrinogen were associated with the occurrence of DCI. ROC curves confirmed the predictive potential of serum A/G, non-surgical treatment, LDH, phosphorus, and plasma fibrinogen levels for DCI in patients with aSAH. In conclusion, serum A/G levels are correlated with DCI in individuals with aSAH, and high serum A/G levels on admission may be associated with the occurrence of DCI.